(untitled) (Revista Direitos Humanos e Democracia, 2026)
This article offers a critical analysis of the influence of gender stereotypes within the Brazilian justice system, examining how patriarchal biases can compromise the impartiality of judicial decisions and the realization of women’s rights. The choice of this topic is justified by the urgent need to address how deeply rooted socio-cultural constructs continue to negatively shape judicial practices, reinforcing inequality and gender-based violence. The study aims to identify the persistence of these stereotypes in national laws and jurisprudence, as well as to assess the incorporation of Inter-American human rights standards into Brazilian legislation and judicial practice. To this end, the research adopts a hypothetical-deductive method and relies on literature review and case law analysis. Paradigmatic cases from the Inter-American Court of Human Rights—such as González et al. ("Cotton Field") v. Mexico, Espinoza González v. Peru, and Barbosa de Souza v. Brazil—are examined, highlighting how gender-biased judicial decisions foster impunity and revictimization. The article also explores the impact of Brazil’s condemnation in the Márcia Barbosa case, emphasizing the creation of the Protocol for Judging with a Gender Perspective and other normative and institutional measures adopted. It concludes that, there have been legal and jurisprudential advances, although challenges to their concrete implementation still persist.